2017
DOI: 10.1371/journal.pone.0185805
|View full text |Cite
|
Sign up to set email alerts
|

Dietary docosahexaenoic acid supplementation prevents the formation of cholesterol oxidation products in arteries from orchidectomized rats

Abstract: Testosterone deficiency has been correlated with increased cardiovascular diseases, which in turn has been associated with increased oxidative stress. Several studies have considered cholesterol oxidation products (COPs) as oxidative stress biomarkers, since some of them play pro-oxidant and pro-inflammatory roles. We have previously described the cardioprotective effects of a dosahexaenoic acid (DHA) supplemented diet on the aortic and mesenteric artery function of orchidectomized rats. The aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…There are now several lines of evidence that 7KC and 7β-OHC have major impacts on the metabolism of cancer cells [250], supporting the concept that chemotherapies targeting metabolism offer promising perspectives for cancer treatment. The rat model has been used to study the metabolism of 7KC [26,50,251], to identify molecules capable of preventing cardiovascular injuries [252] and to determine the impact of some nutrients and aliments on the biogenesis of oxysterols formed by auto-oxidation including 7KC and 7β-OHC [253][254][255]. In addition, using 7KC-containing implants inserted into the anterior chamber of the rat eye, it has been demonstrated that the cytokinic inflammation induced by 7KC mostly occurs through the TLR4 receptor [169].…”
Section: Mousementioning
confidence: 99%
“…There are now several lines of evidence that 7KC and 7β-OHC have major impacts on the metabolism of cancer cells [250], supporting the concept that chemotherapies targeting metabolism offer promising perspectives for cancer treatment. The rat model has been used to study the metabolism of 7KC [26,50,251], to identify molecules capable of preventing cardiovascular injuries [252] and to determine the impact of some nutrients and aliments on the biogenesis of oxysterols formed by auto-oxidation including 7KC and 7β-OHC [253][254][255]. In addition, using 7KC-containing implants inserted into the anterior chamber of the rat eye, it has been demonstrated that the cytokinic inflammation induced by 7KC mostly occurs through the TLR4 receptor [169].…”
Section: Mousementioning
confidence: 99%